Trajectories towards poor mental health: Can general practice contribute to prevention of bad outcomes for young children? - Philip Wilson (European Journal of General Practice)
Factors present in early life account for much of the variation in mental wellbeing in adulthood. In regions where general practitioners (GPs) provide first-contact care for pregnant women and children, there are many opportunities to identify children at risk of later psychiatric problems. These risks are contingent on genetic and antenatal factors, parent–child interaction and family functioning, and are influenced by poverty, the neighbourhood and the educational environment. Depending on the context in which they work, GPs may be able to offer support or referral to specialist services to prevent adverse outcomes. GPs are not able to predict accurately which children will be at developmental risk, so it is important to ensure that systems exist to identify neurodevelopmental problems in the whole population, whether in general practice or elsewhere. When developmental surveillance takes place outside general practice, there are strong arguments for data sharing. Awareness and systematic recording of risk factors for later psychopathology, along with appropriate intervention when available, offer the potential for substantial benefits to population mental health in the long term.